How Plantar Exteroceptive Efficiency Modulates Postural and Oculomotor Control: Inter-Individual Variability - Foisy, Arnaud; Kapoula, Zoï (Frontiers in Human Neuroscience, 2016)
In a previous experiment, we showed that among young and healthy subjects, thin plantar inserts improve postural control and modify vergence amplitudes. In this experiment, however, significant inter-individual variability was observed. We hypothesize that its origin could be attributed to a different reliance upon feet cutaneous afferents. In order to test this hypothesis, we re-analyzed the data relative to 31 young (age 25,7±3,8) and healthy subjects who participated in the first experiment after having classified them into two groups depending on their Plantar Quotient (PQ = Surface area of CoP foam / Surface area of CoP firm ground x100). Foam decreases the information arising from the feet, normally resulting in a PQ>100. Hence, the PQ provides information on the weight of plantar cutaneous afferents used in postural control. Twelve people were Plantar-Independent Subjects, as indicated by a PQ<100. These individuals did not behave like the Normal Plantar Quotient Subjects: they were almost insensitive to the plantar stimulations in terms of postural control and totally insensitive in terms of oculomotor control. We conclude that the inter-individual variability observed in our first experiment is explained by the subjects’ degree of plantar reliance. We propose that plantar independence is a dysfunctional situation revealing an inefficiency in plantar cutaneous afferents. The latter could be due to a latent somatosensory dysfunction generating a noise which prevents the CNS from correctly processing and using feet somatosensory afferents both for balance and vergence control: Plantar Irritating Stimulus. Considering the non-noxious nature and prevalence of this phenomenon, these results can be of great interest to researchers and clinicians who attempt to trigger postural or oculomotor responses through mechanical stimulation of the foot sole.